The Role Of Waste Bank And The Concept Of Green Economy At Universitas Pembangunan Panca Budi - Rangkuty, Dewi Mahrani; Saputra, Muhammad Ilham; Wardah, Siti (International Journal of Economics, Commerce, and Management, 2024)
Environmental problems are becoming an increasingly urgent global issue to be addressed. One of the problems faced is the uncontrolled increase in waste volume, especially in urban areas and large institutions. Universitas Pembangunan Panca Budi, as one of the higher education institutions, has the responsibility to participate in environmental conservation efforts. Waste bank is a program that aims to reduce the volume of waste by collecting, sorting, and recycling waste that can be resold or processed into useful products. There are several benefits of waste banks including, in terms of the environment, reducing the volume of waste disposed of in landfills, reducing pollution, and encouraging recycling. In terms of economy, it can provide economic value from waste, create jobs, and support the circular economy. The various roles of the Waste Bank at the University are as a means of education and environmental awareness that serves as an educational tool for students and staff about the importance of sustainable waste management. The Waste Bank also provides opportunities for students and staff to be actively involved in waste management programs. It not only improves practical skills in waste management but also fosters a sense of social and environmental responsibility. The Waste Bank addresses waste issues that benefit the environment and the economy of the community.